Desakralisasi Upacara 17 Agustus di Istana Merdeka Pada Masa Pemerintahan Joko Widodo: dalam Tinjauan Analisis Wacana Kritis - Novalia Novalia; Rindana Intan Emeilia; Arina Muntazah (Brand Communication, 2022)
This study aimed to describe the text dimensions of the news on the 77th Indonesian Independence Day Commemoration Ceremony in the Kompas.com newspaper with the headline "The Campursari Song Echoes in the Palace, Jokowi is Happy, Iriana and Ministers are Dancing Joyously." This research used desciptive qualitative approach. The text was analyzed using Teun A Van Dijk's critical discourse analysis. The research results showed that the news text contains three dimensions, there are macro structure, super structure, and micro structure